Flexible Conductive Film Based on Copper Nanowires and Its Sensing Applications (International Journal of Scientific Research and Management (IJSRM), 2025)
Copper nanowires have attracted widespread attention due to the abundant availability of raw materials in nature and their high conductivity. Compared with traditional materials such as metals and semiconductors used in sensors, copper nanowire materials possess characteristics such as high thermal conductivity, low heat capacity, resistance to bending, low cost, and better ductility. Copper nanowires were synthesized through the hydrothermal method and uniformly dispersed on the surface of acrylate polymer to form a flexible conductive film, which has excellent flexibility, conductivity, and light transmittance. This film was further used for temperature sensing, and its performance was tested. The flexible conductive film was combined with thermochromic materials to prepare an electrophoretic color-changing device. By adjusting the applied voltage and current, the temperature changes, thereby causing the color change of the thermochromic material.